IMPACT OF INFRASTRUCTURE DEVELOPMENT ON SOCIAL AND ECONOMIC CHANGE IN COMMUNITY - Nurhasna, Faicha; Dani, Ferhan (Bina Bangsa International Journal of Business and Management, 2025)
Infrastructure development has an important role in social change and economic development in a country. The aim of this research is to describe how infrastructure development such as community facilities, roads or bridges can influence the value of life and prosperity of society. The method used is a descriptive method with a literature approach, by analyzing 50 national and international journals that have been published online. Before the paper is published, it must first be discussed with peers and colleagues to get meaningful input. After the paper has been revised according to colleagues' input, the paper is published to add to the development of educational science. Based on the results of the literacy analysis, it can be concluded that the impact of infrastructure development on social and economic changes in society is that, firstly, infrastructure development functions as a social driving factor, which can increase accessibility and connectivity which can encourage further economic growth. Second, although the development of this infrastructure has positive impacts such as improving the quality of life of the community and also providing employment opportunities, on the other hand there are negative impacts such as a lack of community participation in development and potential damage to the environment. Third, the government's strategy in managing social impacts emphasizes the importance of community participation during development implementation and planning. Fourth, a policy evaluation is very important in ensuring that development can empower all communities effectively and efficiently, by evaluating socio-economic impacts and setting policies in accordance with feedback from the community. The recommendation of this research is that the government may have to carry out a comprehensive plan and participate in sustainable infrastructure development, as well as provide assistance to reduce negative impacts on society. Therefore, it is hoped that infrastructure development will be a driver of sustainable social and economic change.